(untitled) (Czech Journal of International Relations, 1967)
The number of studies and books devoted to American strategy has already reached such a scale in the USA that it was difficult for experts to keep a basic overview. Certainly this reason already led to the fact that two anthologies were published here recently and practically at the same time, with the aim of providing a representative selection of works from this area as far as possible. There are of course differences in the selection of the author, in the arrangement and especially in the commentary by the editors of both collections. The Proni collection published by H. A. Kissinger, an expert at the Center for International Policy Research at Harvard University, indicates the thesis of its focus under the title Problems of National Strategy. The second collection also has theses in military strategy, 1 when it is presented under the somewhat different title American Defense Policy. It was published at the initiative of the Air Force Academy, but it was also prepared by the political science department here. It is certainly not by chance that the introduction emphasizes that he understands the researched area as a part of political science.